2017
DOI: 10.3332/ecancer.2017.714
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer and related epigenetic alterations

Abstract: Gastric cancer, a malignant and highly proliferative condition, has significantly affected a large population around the globe and is known to be caused by various factors including genetic, epigenetic, and environmental influences. Though the global trend of these cancers is declining, an increase in its frequency is still a threat because of changing lifestyles and dietary habits. However, genetic and epigenetic alterations related to gastric cancers also have an equivalent contribution towards carcinogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 60 publications
0
38
0
1
Order By: Relevance
“…Several epidemiological studies have demonstrated that dietary factors and DNA methylation could independently and significantly influence the progression of GC , while dietary factors play an important role not only in tumorigenesis but also in inducing DNA methylation , hence their interactions and combinations were explored in this study subsequently. Results showed that significant combinations were obviously observed between the dietary factors and KIBRA methylation on the GC risk, but no interactions were found.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have demonstrated that dietary factors and DNA methylation could independently and significantly influence the progression of GC , while dietary factors play an important role not only in tumorigenesis but also in inducing DNA methylation , hence their interactions and combinations were explored in this study subsequently. Results showed that significant combinations were obviously observed between the dietary factors and KIBRA methylation on the GC risk, but no interactions were found.…”
Section: Discussionmentioning
confidence: 99%
“…26 No 2: 157-163 [24]. The pathogenesis of gastric cancer is the result of the interaction between environmental and genetic factors [24,25].…”
Section: Geneticsmentioning
confidence: 99%
“…Activation of K-ras and β-catenin oncogenes, mutation of the p53 tumor suppressor gene and MSI have been associated with both histological types. Amplification of C-erb and C-met genes has been found in about 10% of both histological types [24,25]. Somatic mutation of CDH1 has been associated with diffuse gastric cancer specifically [24,25].…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations